Transformer Isolated Buck-Boost Converters - Barry W. Williams (Renewable Energy and Sustainable Development)
Of the single-switch dc-to-dc converters, those with the buck-boost voltage transfer function offer most potential for transformer coupling, hence isolation, at the kilowatt level. This paper highlights the limitations of the traditional magnetic coupled, buck-boost topology. Then four split-capacitor transformer-coupled topologies (specifically the Cuk, sepic, zeta, and a new, converters) with a common ac equivalent circuit are explored, that do not temporarily store core magnetic energy as does the traditional isolated buck-boost converter nor have a core dc magnetizing current bias, as with the sepic and zeta transformer coupled topologies. Core dc bias capacitive voltage compensation is a practical design constraint in three of the four topologies, while all four must cater for stray and leakage inductance effects. Simulations and experimental results for the new converter at 408W support the transformer-coupled, single-switch dc-to-dc converter concepts investigated.